Healthcare expenditures among community-dwelling adults with thyroid cancer in the United States: A propensity score matched analysis. Issue 6 (June 2019) - Bhattacharjee, Sandipan; Khobrani, Moteb; Alrabiah, Ziyad; Bilal, Jawad; Riaz, Irbaz Bin
Abstract: Objective: This study assessed the excess healthcare expenditures and factors associated with it among community-dwelling adults with thyroid cancer compared to non-cancer controls in the United States. Method: A retrospective, cross-sectional, matched case-control study design was used by pooling multiple years of Medical Expenditure Panel Survey (MEPS) data (2002–2012). The eligible study sample comprised of adults (age ≥18 years), who were alive during the calendar year and reported positive healthcare expenditure. The case group consisted of adults with thyroid cancer only while the control group consisted of adults who did not have any form of cancer. Total and subtypes of mean annual healthcare expenditures comprised the main study outcome. We also calculated the total and subtypes of out-of-pocket (OOP) expenditures as well as OOP as a percentage of household income. Ordinary Least Square (OLS) regressions on log-transformed expenditures were conducted to elucidate the influence of different factors on healthcare expenditures among adults with thyroid cancer. Results: The yearly average total healthcare expenditures among adults with thyroid cancer was significantly higher compared to propensity score matched controls ($9, 585 vs. $5, 830, p < 0.001). Similar observations were found in terms of inpatient, and outpatient expenditures. Functional status as well as comorbid conditions were significantly associated with excess expenditures. The yearly average total OOP expenditure for adults with thyroid cancer was significantly higher compared to matched controls ($1, 425 vs. $974, p < 0.001), with major differences observed in inpatient OOP ($178 vs. $24, p = 0.003), outpatient OOP ($435vs. $256, p < 0.001), and prescription OOP ($554 vs. $423, p < 0.001) expenditures. There was a significant (p < 0.001) difference between the average OOP as a percentage of household income between adults with thyroid cancer (Mean: 7.54%, S.E: 1.52%) and matched controls (Mean: 5.80%, S.E: 0.47%). Conclusions: Our findings suggest that holistic care approach could be helpful to significantly reduce the economic burden in this population. Viable strategies such as limits on OOP costs are required to minimize this high OOP burden among cancer survivors and their families.